Sexual identity modifies the association between bullying and suicide planning among adolescents with same-sex sexual partners. Issue 3 (3rd July 2019) - Turpin, Rodman; Boekeloo, Bradley; Dyer, Typhanye
Abstract: Heterosexual adolescents with same-sex sexual partners may be at increased risk for psychological distress from victimization; this may lead to suicidality. We tested if sexual identity modified the association between bullying at school and suicide planning among adolescents with the same-sex sexual partners. We sampled 924 youth with same-sex sexual partners from the 2015 Youth Risk Behavior Survey, testing the association between bullying and suicide planning using log-binomial regression with sexual identity interactions. Sexual identity modified this association, with the greatest association among heterosexual participants (PR = 4.01, 95% CI 2.60–6.18). Anti-homophobia messaging and intervention programs that target these youth may be needed.